TRANSLATION ANALYSIS OF FIGURATIVE LANGUAGE IN TO KILL A MOCKINGBIRD NOVEL - Muhamad Gilang Abdumaula; Evert H. Hilman (PROJECT (Professional Journal of English Education), 2022)
This study investigates the translation methods used to translate figurative languages in the novel from English to Indonesian and the translation quality assessment. The main theory used to help find the answers in the process of analyzing are Newmark and Nababan et al., along with other supporting theories. Qualitative descriptive and focus group discussion are used as a research method. The results showed that the most frequent translation method is literal translation (51.47%), free translation (23.53%), idiomatic translation (18.38%), and word-for-word translation (6.62%). In terms of translation quality assessment, overall data implies high accuracy level, high acceptability level, and high readability level. Keywords:  Figurative Language, Translation Method, Translation Quality Assessment